MENANTANG STEREOTIP GENDER DALAM FILM PINK (2016) TENTANG KEKERASAN SEKSUAL: KAJIAN FEMENISME RADIKAL - Nensilianti Nensilianti; Ridwan Ridwan; Resky Amaliah M (Diksatrasia : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to analyze the meaning, message, and representation of women in the film Pink using a radical feminist perspective. Through a qualitative approach with a textual analysis method, the research explores how the film critiques the patriarchal system and gender stereotypes in cases of sexual violence. The film serves not only as entertainment but also as a tool for education and advocacy, promoting awareness of the importance of gender equality and justice for victims of sexual violence. Pink highlights the issue of sexual violence and gender injustice rooted in the patriarchal system. It portrays how women are often blamed in cases of sexual harassment, while male perpetrators receive social protection. Radical feminism is employed to analyze the patriarchal structures presented in the film. The findings of this study reveal how women are frequently blamed in cases of sexual harassment, while male perpetrators are socially protected within the narrative of the film.